Модель Хекшера–Оліна–Самуельсона: теоретичний базис і умови застосування - Босак, А. О.; Найчук-Хрущ, М. Б.; Bosak, A. O.; Naychuk-Khrushch, M. B. (Видавництво Львівської політехніки, 2022)
Досліджено особливості використання моделі Хекшера – Оліна – Самуельсона та її окремих допущень. Виявлено чинники впливу на процес вирівнювання відносних та абсолютних цін факторів виробництва. Перевірено статистичні зв’язки показників факторів виробництва і параметрів міжнародної торгівлі окремих країн та їх експортно-орієнтованих галузей. Сформовано рекомендації щодо використання моделі Хекшера – Оліна – Самуельсона для розвитку міжнародної економічної діяльності України.

The Heckscher – Ohlin – Samuelson model provides a mathematical proof of the possibility of equalizing the relative and absolute prices for production factors in international trade with certain assumptions. However, in practice, these assumptions are not followed. Therefore, there is a need to adjust the parameters of the model by calculating the indicators of cost estimation and the use of production factors. Therefore, the purpose of the research is to generalize the theoretical provisions of the Heckscher – Ohlin – Samuelson model in order to find the possibilities of its application in the conditions of the postwar economic recovery of Ukraine. The main research methods were theoretical generalization, economic and statistical analysis, multivariate linear regression. In the process of the research, several partial tasks were performed: 1) systematizing the views of scientists regarding methods of adjusting the parameters of the Heckscher – Ohlin –Samuelson model; 2) the existence of a statistical relationship between the factor saturation of the economies of individual countries with the indicators of their foreign trade and changes in the prices of production factors; 3) recommendations for the application of the Heckscher – Ohlin – Samuelson model in the conditions of the post-war economic recovery of Ukraine. A comparison of the volumes of available labor and capital investment were made for 2020. And it proves that industrialized countries are excessively capital-saturated, but the calculation of K/L ratios still does not explain the structure of their international trade. At the same time, for some relatively developed countries, including Ukraine, the K/L ratio is “paradoxical”. The results of the regression analysis of production factors and foreign trade indicators of 30 countries, of the largest volume of capital investments, prove the existence of a relatively close connection of K/L ratios with indicators of export-import and their growth, in condition of the involving of correction coefficients into the basic Heckscher – Ohlin – Samuelson model. The main condition for applying the tools of the Heckscher – Ohlin – Samuelson model in modern practice is the mitigation of its assumptions regarding the homogeneity of production factors, their full use, and the limitation of their international mobility. In addition, it is necessary to ensure the identity of the measurement parameters of production factors in different statistical systems, taking into account the time factor and exchange rate differences. The practical significance of the study is that in the conditions of the post-war economic recovery of Ukraine, most of the assumptions of the Heckscher – Ohlin – Samuelson model are nullified. Its explained by situation that state will have to introduce strict restrictions on the movement of production factors and international trade for some time. This allows to form real statistics on the use of production factors and, on its basis, to carry out programming of Ukraine's international trade.
The Neckscher–Ohlin–Samuelson model: theoretical basis and conditions of application
Keywords: теорія Хекшера – Оліна; модель Хекшера – Оліна – Самуельсона; модель Хекшера – Оліна – Ванека; фактори виробництва; капіталомісткість; працемісткість; відносні ціни факторів виробництва; вирівнювання цін на фактори виробництва; Heckscher – Ohlin theory; Heckscher – Ohlin – Samuelson model; Heckscher – Ohlin – Vanek model; factors of production; capital intensity; labor intensity; relative factors prices; factor price equalization theorem (FPET); 339.5.018.62